Human Resource Management in Sport and Recreation - Chelladurai, P.; Kim, Amy (Champaign: Human Kinetics, 2023)
"This textbook provides readers a foundation in research and application of human resource management in the sport and recreation industries. It explains essential concepts in human resources specific to the sport and recreation industries. It focuses on the three groups of people who constitute human resources in sport and recreation organizations: paid professional workers, volunteers, and clients"--
"The authoritative text for current and future practitioners of human resources management in the sport and recreation industries is back in a revised fourth edition. This new edition addresses contemporary issues that organizations face today. Human Resource Management in Sport and Recreation, Fourth Edition, offers a solid foundation in research and application, and it provides a holistic perspective of human resource management by bringing together the three groups of people who constitute human resources across sport and recreation organizations: paid professionals, volunteers, and the clients themselves.Dr. Packianathan Chelladurai, a pioneer in the field of sport management, is joined by Dr. Amy Chan Hyung Kim to lend expertise gained from more than four decades of teaching human resource management. They guide students through four parts, starting with an outline of the common characteristics of the three groups of people that make up human resources. Part II focuses on individual differences among people and how those differences affect behavior within organizations. In part III, students will explore organizational processes, and part IV discusses two significant outcomes expected of human resource practices: satisfaction and commitment. The conclusion uses 10 guiding themes to bring all the concepts together with an eye toward the future of the field.Updated to address current topics such as social issues and diversity, the fourth edition reflects the increasing complexity of human resource management across the field of recreation and sport. Modern issues and their real-world implications are represented throughout the text with recurring sidebars.Diversity Management of Human Resources: offer insights into how and when to promote and manage diversityCrisis Management: address the role of human resource management during emergency situations, such as the COVID-19 pandemicSocial Phenomena and Human Resource Management: assess the impact of major social events or movementsLegal Considerations in Human Resource Management: focus on legal matters in the fieldFrom the Field: provide professional insights from leading practitioners across a variety of sport contextsCase studies, discussion questions, and activities provide further opportunity for students to understand relevant research with real-world application of concepts.With clear explanations of concepts and current practices in human resources across the sport and recreation industries, Human Resource Management in Sport and Recreation, Fourth Edition, is a valuable resource for future and current practitioners alike"--
Includes bibliographical references and index.
Machine generated contents note: Part I. Human Resources in Sport and Recreation -- Chapter 1. Significance of Human Resources -- Service Operations -- Sport and Recreation Services -- Paid and Volunteer Workers -- Clients as Human Resources -- A Model of Human Resource Management -- Chapter Pursuits -- Chapter 2. Volunteers and Volunteerism -- The Need for Volunteerism -- Voluntary Organizations -- People Who Volunteer -- Why People Volunteer -- Altruism and Volunteerism -- Role of the Sport or Recreation Manager -- Chapter Pursuits -- Chapter 3. Professionals and Professionalism -- Original Definition of a Profession -- Process of Professionalization -- Semiprofessions, Mimic Professions, and Deprofessionalization -- Professional Status of Sport Management -- Professionalism and Volunteerism -- Role of the Sport or Recreation Manager -- Chapter Pursuits -- Chapter 4. Clients as Human Resources -- Customer as Input, Throughput, and Output -- Customer Participation in Sport and Recreation Services -- Client Motives for Participation -- Role of the Sport or Recreation Manager -- Chapter Pursuits -- Part II. Individual Differences in Human Resources -- Chapter 5. Abilities -- Issues in the Study of Ability -- Cognitive Abilities -- Emotional Intelligence -- Role of the Sport or Recreation Manager -- Chapter Pursuits -- Chapter 6. Personality -- Determinants of Personality -- Type Theories -- Trait Theories -- Personality and Organizational Behavior -- Role of the Sport or Recreation Manager -- Chapter Pursuits -- Chapter 7. Values -- Values, Beliefs, Attitudes, and Norms -- Sources of Values -- Terminal and Instrumental Values -- Hierarchy of Values -- Value Types -- Functions of Values -- Values in Organizations -- National Values and Sport -- Role of the Sport or Recreation Manager -- Chapter Pursuits -- Chapter 8. Motivation -- A Model of Motivation -- Other Theories of Motivation -- Motivation as Personal Investment -- Role of the Sport or Recreation Manager -- Chapter Pursuits -- Part III. Human Resource Practices -- Chapter 9. Organizational Justice -- Distributive Justice -- Procedural Justice -- Interactional Justice -- Role of the Sport or Recreation Manager -- Chapter Pursuits -- Chapter 10. Job Design -- Job Design Strategies -- Task Attributes -- Motivational Properties of Tasks -- Implementing Task Attributes -- Task Attributes and Individual Differences -- Other Approaches to Job Design -- Task Dependence, Coordination, and Variability -- Role of the Sport or Recreation Manager -- Chapter Pursuits -- Chapter 11. Staffing and Career Considerations -- Purposes of Staffing -- Focus of Staffing -- Matching People and Jobs -- Psychological Contract -- Career Considerations -- Mentoring -- Role of the Sport or Recreation Manager -- Chapter Pursuits -- Chapter 12. Leadership -- Leader Behavior -- Multidimensional Model of Leadership -- Transformational, Transactional, Servant, and Authentic Leadership -- Leadership and Decision Making -- Role of the Sport or Recreation Manager -- Chapter Pursuits -- Chapter 13. Performance Appraisal -- Purposes of Performance Appraisal -- What Should Be Evaluated -- When to Conduct Performance Appraisal -- Who Should Do the Appraisal -- Errors in Rating -- Role of the Sport or Recreation Manager -- Chapter Pursuits -- Chapter 14. Reward Systems -- Purposes of Reward Systems -- Types of Rewards -- Bases of Rewards -- Reward Systems and Member Preferences -- Role of the Sport or Recreation Manager -- Chapter Pursuits -- Chapter 15. Internal Marketing -- Forms of Marketing -- Process Versus People Orientation in Internal Marketing -- Marketing Principles in Internal Operations -- Functions of Internal Marketing -- Issues in Internal Marketing -- Role of the Sport or Recreation Manager -- Chapter Pursuits -- Part IV. Attitudinal Outcomes -- Chapter 16. Satisfaction -- Theories of Job Satisfaction -- Satisfaction With Volunteer Work -- Participant Satisfaction -- Measurement of Satisfaction -- Role of the Sport or Recreation Manager -- Chapter Pursuits -- Chapter 17. Commitment -- Multidimensionality of Organizational Commitment -- Occupational Commitment -- Development and Effects of Organizational Commitment -- Correlates of Organizational Commitment -- Role of the Sport or Recreation Manager -- Chapter Pursuits -- Conclusion. The Future of Human Resource Management in Sport and Recreation-Guiding Themes.
Keywords: Sports administration; Personnel management; SPORTS & RECREATION / General; BUSINESS & ECONOMICS / Human Resources & Personnel Management